Study on Phylogenetic Status of Javan Plover Bird (Charadrius, Charadriidae, Charadriiformes) through DNA Barcoding Analysis - Ashari, Hidayat; Astuti, Dwi (Biosaintifika: Journal of Biology & Biology Education, 2017)
Javan Plover named Charadrius javanicus is taxonomically under controversy and phylogenetically unresolved yet. Through an analysis of DNA barcode, this study aims (1) to confirm whether Javan Plover is separated species named Charadrius javanicus or a subspecies of C. alexandrinus which named C. a. javanicus and (2) to determine a relationship within this genus. Totally 666 bp DNA sequences of COI barcode gene were analyzed. The results showed that a sequence divergence between Javan Plover and C. alexandrinus alexandrinus was only 1.2%, while sequence divergences between C.a.alexandrinus and others species, or between Javan Plover and others species were ranged from 9-12%. Neighbour-joining (NJ) and maximum-parsimony (MP) analyses showed that all individuals of both Javan Plover and Kenith Plover were clustered together, and supported by 99 % and 100 % of bootstrap value in NJ and MP, respectively. This study tends to support the previous findings that Javan Plover was not a separated species named C. javanicus, but it was as a subspecies of C. alexandrinus; named C. a. javanicus. There were two groups of Plover in this study; (C. leschenaultii and C. javanicus + C.a.alexandrinus), and (C.dubius and C. melodus + C. semipalmatus). DNA barcoding analysis can give certainty taxonomic status of the bird. Then, this study has implication as a basic data that can be used to provide and support the planning of Javan plover conservation programs.